2002
DOI: 10.1007/s00284-001-0110-9
|View full text |Cite
|
Sign up to set email alerts
|

The Ketolide Antibiotic ABT-773 Is a Specific Inhibitor of Translation and 50S Ribosomal Subunit Formation in Streptococcus pneumoniae Cells

Abstract: ABT-773 is a new 3-keto macrolide antibiotic that has been shown to be very effective against infections by Gram-positive microorganisms. This work examines its inhibitory effects in cells of Streptococcus pneumoniae. ABT-773 caused a proportional decline in cell growth rates and viability with an IC(50) of 5 ng/ml. Protein synthesis in these cells was reduced by 50% at an antibiotic concentration of 2.5 ng/ml. This compound was also found to be a very effective inhibitor of the formation of the 50S ribosomal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
5

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 33 publications
1
16
0
5
Order By: Relevance
“…The IC 50 of 7.5 ng/ml found for inhibition of translation and 50S assembly is comparable to the IC 50 s of 5 ng/ml observed for cethromycin (9) and 15 ng/ml measured for telithromycin (10). The solithromycin IC 50 is consistent with MIC 50 values of 15 to 60 ng/ml reported in various studies of S. pneumoniae strains (8,(21)(22)(23)(24)(25).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The IC 50 of 7.5 ng/ml found for inhibition of translation and 50S assembly is comparable to the IC 50 s of 5 ng/ml observed for cethromycin (9) and 15 ng/ml measured for telithromycin (10). The solithromycin IC 50 is consistent with MIC 50 values of 15 to 60 ng/ml reported in various studies of S. pneumoniae strains (8,(21)(22)(23)(24)(25).…”
Section: Discussionsupporting
confidence: 77%
“…Methicillin-susceptible Staphylococcus aureus (MSSA) strain RN1786 was obtained from Richard Novick (New York University), and a clinical isolate of methicillin-resistant S. aureus (MRSA) (strain A1024) was provided by Joyce Sutcliffe (Tetraphase Pharmaceuticals) (12). H. influenzae strain CDC G-79 (13) and S. pneumoniae strain ATCC 49619 (9,10) 175 Ci/mmol) were purchased from American Radiochemicals (St. Louis, MO) and MP Biomedical (Solon, OH), respectively. Solithromycin was provided by Cempra Pharmaceuticals (Chapel Hill, NC) and was dissolved at 1 mg/ml in acetic acid at a pH of 5.5.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The macrolides form hydrogen bonds with the 23S rRNA at domains II and V and thus inhibit bacterial protein synthesis. Ketolides are known to bypass macrolide resistant mechanisms by improving ribosome binding affinity, especially binding to domain II and evading macrolide efflux mechanisms 60, 61. The structure-activity relationship is paramount in ketolide mechanism of action.…”
Section: Antibacterial Drugsmentioning
confidence: 99%
“…It has been suggested that the inhibition of 50S assembly is lethal for bacteria because of RNase degradation of the ribosomal RNAs (27,30,(32)(33)(34), but no causal link has been established, and inhibitors of 50S assembly that are merely bacteriostatic also cause the degradation of rRNA (155).…”
Section: Rrna Degradation and Lethalitymentioning
confidence: 99%